Aplikasi Sistem Pakar Diagnosa Penyakit Kejiwaan Berbasis Web Menggunakan Forward Chaining dan Certainty Factor - Fitri Nuraeni; Raden Erwin Gunadhi Rahayu; Muhamad Rifki Renaldi; Risa Aisyah (Jurnal Algoritma, 2022)
Patients with psychiatric disorders in Indonesia have increased every year, this is due to the lack of public knowledge of the symptoms and types of psychiatric disorders themselves, plus mental health facilities which are still limited in number, and the number of psychiatric specialists is relatively small and the cost of treatment is relatively not cheap. . In the current technological era, computer applications have been applied to all fields including the health sector, so to diagnose psychiatric disorders a computer application can be made that has the ability to diagnose like a psychiatrist. Therefore, in this study an expert system application was built that applied the forward chaining inference method and certainty factor, where the application was developed using the expert system development life cycle (ESDLC) method. The results of this study are a website-based expert system application with a knowledge base consisting of 2 diagnoseable diseases, namely Schizophrenia and Bipolar, as well as 22 disease symptoms. This application has been tested with 100% accuracy in 10 cases compared between the results of expert diagnoses and the results of expert system application inferences.